Upaya Win-win Solution antara Pengusaha dan Pekerja akibat Penurunan Omset Perusahaan yang terdampak Pandemi Covid-19 - Habibi, Nabil; Arlin Andini, Syavira; Sinaga, Tesalonika Natasya; Nainggolan, Theresia Naomi; Puspita, Vira Della (Journal of Industrial Relations Studies, 2025)
The COVID-19 pandemic has caused serious disruptions to business activities in various sectors, including PT Tempa Jaya, Pulogadung. The drastic decline in the company's turnover resulted in a policy of adjusting employee wages as a form of efficiency. This study uses an empirical legal method with an interview approach to management, permanent workers, and contract workers, to assess the extent to which the wage policy is in accordance with applicable labor law principles. The results of the study show that wage cuts were carried out without going through a deliberation mechanism or bipartite agreement as stipulated in laws and regulations. This policy has a negative impact on work motivation and the economic welfare of workers, especially contract workers who do not have long-term employment security. This study recommends improving industrial communication, utilizing flexible work policies, and strengthening the government's role in supervising the implementation of worker protection during the crisis. A participatory justice-based approach and a win-win solution are essential in maintaining healthy industrial relations in times of uncertainty